Continuous recording of pulmonary artery pressure in unrestricted subjects. Issue 4 (April 1984) - Ikram, H; Richards, A M; Hamilton, E J; Nicholls, M G
Abstract : Continuous ambulatory pulmonary artery pressures were recorded using a conventional No 5 French Goodale-Lubin filled catheter linked to the Oxford Medilog system of a portable transducer-perfusion unit and miniaturised recorder. Data retrieval and analysis were performed using a PB2 Medilog playback unit linked to a PDP 11 computer system. The total system has a frequency response linear to 8 Hz allowing accurate pressure recording over the full range of heart rates. Ten recordings in 10 patients yielded artefact free data for 80% or more of the recorded period. This inexpensive reliable method allows pulmonary artery pressures to be recorded in unrestricted subjects.